Synthesis of New Schiff Base from Natural Products for Remediation of Water Pollution with Heavy Metals in Industrial Areas - Reham Hassan; Hassan Arida; Manal Montasser; Nehad Abdel Latif (Journal of Chemistry)
A resin of [5-((E)-1-(ethylimino) ethyl)-4, 7-dimethoxy benzofuran-6-ol] Schiff base (EEDB) was prepared, characterized, and successfully applied in the removal of Cu (II) ions from aqueous real samples. While the metal cation was detected using ICP-OES, the prepared Schiff base resin was characterized by means of FTIR, 1HNMR, mass spectral data, and elemental analysis. Various factors affecting the uptake behavior such as pH (2–12), contact time, effect of initial metal concentration (10–250 ppm), and effect of Schiff base weight (0.1–1.5 gm) were studied. The adsorption process was relatively fast and equilibrium was established after about 60 min. The optimum initial pH was 8.0 at a metal ion concentration (100 ppm). Under the optimized conditions, the removal of Cu (II) from real samples of tap water was applied and the removal efficiency reached nearly 85%. The biological activity for Schiff base was also investigated. The results showed that there is no significant difference between the effects of Schiff base on serum (alanine amino transferase) ALT and creatinine concentration activities in treated mice and control, at confidence limits 95%.